Word Formation in Hippolytus’s Manuscript Dictionary (1711– 1712): Lexicographic Tradition and New Features - Andreja (Jezikoslovni zapiski, 2023)
This article presents the word-formational character of Slovenian equivalents of German and Latin headwords in Hippolytus’s dictionary Dictionarium trilingue (1711–1712). Selected examples of Hippolytus’s word families were compared with older and more recent lexicographic sources from the sixteenth to the twenty-first century, and their complexity was determined. Using sample material, all adjectival derivatives starting with l and m, and adjectival compounds starting with k, l, and m with a two-morpheme infix plus suffix were extracted from the dictionary’s list of entries. Based on comparison, their continuity in standard Slovenian from the sixteenth to the twenty-first century was determined in addition to their word-formational variance, archaicism, disappearance, or revitalization.